As seen exhibitions that made architecture and design history - Ryan, Zoë 1976-; Antonelli, Paola 1963-; Boelen, Jan (The Art Institute of Chicago, 2017)
"Exhibitions have long played a crucial role in defining disciplinary histories. This volume examines the impact of eleven groundbreaking architecture and design exhibitions held between 1956 and 2006, revealing the different ways they have shaped how these disciplines are understood and practiced today. Featuring written and photographic descriptions of the shows and essays from noted curators, scholars, critics, designers, and artists, As Seen: Exhibitions that Made Architecture and Design History explores the multifaceted ways in which exhibitions have reflected on contemporary dilemmas and opened up new processes and ways of working. Providing a fresh perspective on some of the most important exhibitions of the 20th century from America, Europe, and Japan, including This Is Tomorrow, Expo '70, and Massive Change, this book offers a new framework for thinking about how exhibitions can function as a transformative force in the field of architecture and design"...